Commercial hybrids and mutant genotypes reveal complex protective roles for inducible terpenoid defenses in maize - Christensen, Shawn A (Journal of experimental botany, 2018)
Plant defense research is facilitated by the use of genome-sequenced inbred lines; however, a foundational knowledge of interactions in commercial hybrids remains relevant to understanding mechanisms present in crops. Using an array of commercial maize hybrids, we quantified the accumulation patterns of defense-related metabolites and phytohormones in tissues challenged with diverse fungal pathogens. Across hybrids, Southern leaf blight (Cochliobolus heterostrophus) strongly elicited specific sesqui- and diterpenoid defenses, namely zealexin A4 (ZA4) and kauralexin diacids, compared with the stalk-rotting agents Fusarium graminearum and Colletotrichum graminicola. With respect to biological activity, ZA4 and kauralexin diacids demonstrated potent antimicrobial action against F. graminearum. Unexpectedly, ZA4 displayed an opposite effect on C. graminicola by promoting growth. Overall, a negative correlation was observed between total analyzed terpenoids and fungal growth. Statistical analyses highlighted kauralexin A3 and abscisic acid as metabolites most associated with fungal suppression. As an empirical test, mutants of the ent-copalyl diphosphate synthase Anther ear 2 (An2) lacking kauralexin biosynthetic capacity displayed increased susceptibility to C. heterostrophus and Fusarium verticillioides. Our results highlight a widely occurring defensive function of acidic terpenoids in commercial hybrids and the complex nature of elicited pathway products that display selective activities on fungal pathogen species